Reversible supraventricular tachycardia complicating diabetic ketoacidosis in an adult patient: A case report (Indian Journal of Case Reports, 2021)
Diabetic ketoacidosis (DKA) is a commonly encountered serious acute metabolic complication of diabetes mellitus (DM) in adolescents and young adults. It is traditionally associated with poorly treated or newly diagnosed type 1 DM, however, in the setting of type 2 DM, inadequate insulin treatment, non-compliance to treatment, newly diagnosed DM, acute illnesses, drugs, and extreme stress can precipitate DKA. We report the case of a 42-year-old known diabetic of 7 years duration with a family history of DM who presented with a two-week history of difficulty in breathing, polyuria, and vomiting. On further examination, pulse rate was 220 beats per minute, respiratory rate 40 cycles per minute, temperature 38.4’C. Random blood sugar was 18.1mmol/l with ketonuria ++. Severe acidosis and mild hypokalemia were noted with her electrocardiogram (ECG) showing supraventricular tachycardia. She was managed and discharged in stable condition with a normal ECG after 20 days on admission to continue basal and pre-meal insulin at home. Adequate diabetic education was conducted and follow-up with endocrinology and cardiology units was advised.